2014
DOI: 10.1007/s11356-014-3320-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting degradation of dimethyl sulfoxide (DMSO) by fluidized-bed Fenton process

Abstract: In this study, the target compound is dimethyl sulfoxide (DMSO), which is used as a photoresist stripping solvent in the semiconductor and thin-film transistor liquid crystal display (TFT-LCD) manufacturing processes. The effects of the operating parameters (pH, Fe(2+) and H2O2 concentrations) on the degradation of DMSO in the fluidized-bed Fenton process were examined. This study used the Box-Behnken design (BBD) to investigate the optimum conditions of DMSO degradation. The highest DMSO removal was 98 % for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…8 Bellotindos et al investigated the degradation of DMSO by using the Fenton process in a fluidized-bed reactor, and 98% DMSO was degraded after 120 min under the optimum conditions of pH 3, 5 mM Fe 2+ , 60 mM H 2 O 2 , and 1 mM DMSO. 9 Matira et al also studied the degradation of DMSO in the fluidized-bed Fenton process and confirmed that methanesulfinate, methanesulfonate, formaldehyde, and formate were the intermediates of DMSO degradation. 10 Among these intermediates, methanesulfonate is the most difficult to degrade, and it is recalcitrant to Fenton degradation and contributed most to the residual TOC.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…8 Bellotindos et al investigated the degradation of DMSO by using the Fenton process in a fluidized-bed reactor, and 98% DMSO was degraded after 120 min under the optimum conditions of pH 3, 5 mM Fe 2+ , 60 mM H 2 O 2 , and 1 mM DMSO. 9 Matira et al also studied the degradation of DMSO in the fluidized-bed Fenton process and confirmed that methanesulfinate, methanesulfonate, formaldehyde, and formate were the intermediates of DMSO degradation. 10 Among these intermediates, methanesulfonate is the most difficult to degrade, and it is recalcitrant to Fenton degradation and contributed most to the residual TOC.…”
Section: Introductionmentioning
confidence: 94%
“…Among these methods, the Fenton process is the most widely employed strategy for the oxidative removal of DMSO from wastewater. For example, Luna et al investigated the degradation of DMSO in a double-cathode electro-Fenton reactor and found that the complete degradation of DMSO was obtained under experimental conditions of 5 mM DMSO, pH 2, 27 mM H 2 O 2 , 2.14 mM Fe 2+ , and 1.5 A current density after 120 min . Bellotindos et al investigated the degradation of DMSO by using the Fenton process in a fluidized-bed reactor, and 98% DMSO was degraded after 120 min under the optimum conditions of pH 3, 5 mM Fe 2+ , 60 mM H 2 O 2 , and 1 mM DMSO . Matira et al also studied the degradation of DMSO in the fluidized-bed Fenton process and confirmed that methanesulfinate, methanesulfonate, formaldehyde, and formate were the intermediates of DMSO degradation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that DMSO can generate radicals upon interacting with reactive oxygen species (ROS) or in the presence of a base. [66][67][68][69][70][71][72][73][74] The radical generation rate depends on temperature following the Arrhenius equation. Upon lowering the reaction temperature from 100 °C to 50 °C, the concentration of radicals decreased, and the number of polymer chain branching/ crosslinking events decreased.…”
Section: Papermentioning
confidence: 99%
“…DMSO can serve as an effective source to generate various radical species. [66][67][68][69][70][71][72][73][74] To facilitate the radical generation, [75][76][77][78][79] copper sulfide (CuS) nanoparticles (NPs) were synthesized and used as catalysts. The DMSO-generated radicals participated in the chain cleavage reaction, leading to competing processes of oligomerization and branching/crosslinking depending on the reaction temperature and solution heterogeneity.…”
Section: Introductionmentioning
confidence: 99%